TENDENCIES OF EXPORT OF GOODS OF UKRAINE IN CONDITIONS OF EUROPEAN INTEGRATION - Verbytska , H.L. (The actual problems of regional economy development, 2017)
The article aims to study the trends of export of goods of Ukraine in conditions of European integration. The purpose is to examine the export trends of goods of Ukraine in conditions of European integration; to determine the prospects of improving the export policy of Ukraine. In the process of research the following methods were used: Economics and statistics (in the study of trends of export of goods of Ukraine in conditions of European integration); analytical and logical (in determining the directions of the export policy of the Ukrainian government). The following results are obtained: the structure and trends of exports of goods Ukraine; analyzes the current processes of European integration and the changes that have occurred in this regard in the field of international trade; the identified negative factors affecting the condition of foreign trade of Ukraine. Scientific novelty of the research is to use an integrated approach to the justification of directions of improvement of the export policy of Ukraine, the implementation of which will improve the efficiency of integration into the world economy. The results of research aimed at solving the problems of the passive trade balance of the domestic economy. They can be used in the formation of government export policy.